Garden protection / Arif Mohamad Johari, Muhammad Rashid Khairuddin and Zaid Hariz Zainuddin - Mohamad Johari, Arif; Khairuddin, Muhammad Rashid; Zainuddin, Zaid Hariz (2013)
Garden protection is design to provide protection for small garden. It also design for an energy saving and low cost instruction. This project consists of three different sensors which are LDR, Vibration and Infrared sensor. Each sensor has their owned functionality and act as the security for the garden. Firstly, LED will turn ON as there are no light sensed by the LDR. We use two layer sensor which is Infrared and Piezo element. Infrared is use to detect the motion of animal that pass through the sensor. Piezo is used to detect the vibration of anything that step on it. Both of the sensors will turn on the buzzer to chase away the animals. As when the night comes, the LED that represent bulb will light up the front gate as LDR will only activate when no light is detected. We have some difficulty while doing the project, as we are using ISIS PROTEUS software, there is some component that is not found in the software, but some way, we overcome the problem.